Altered Innate Immunity and Damaged Epithelial Integrity in Vaginal Microbial Dysbiosis - Cheu, Ryan K.; Mohammadi, Avid; Schifanella, Luca; Broedlow, Courtney; Driscoll, Connor B.; Miller, Charlene J.; Reeves, R. Keith; Yudin, Mark H.; Hensley-McBain, Tiffany; Kaul, Rupert; Klatt, Nichole R. (Frontiers in Reproductive Health, 2022)
The role of neutrophils relative to vaginal dysbiosis is unclear. We hypothesize that bacterial vaginosis (BV)-associated bacteria may induce the activation and accumulation of mucosal neutrophils within the female reproductive tract (FRT), resulting in epithelial barrier damage. We collected endocervical cytobrushes from women with and without BV and assessed bacteria community type and frequency/functional phenotypes of neutrophils. We performed in vitro whole blood co-cultures with BV-associated bacteria and healthy vaginal commensals and assessed their impact on epithelial integrity using transepithelial electrical resistance. We demonstrated increased neutrophil frequency (p<0.0001), activation (p<0.0001), and prolonged lifespan (p<0.0001) in the cytobrushes from women with non-Lactobacillus dominant (nLD) communities. Our in-vitro co-cultures confirmed these results and identified significant barrier damage in the presence of neutrophils and G. vaginalis. Here, we demonstrate that BV-associated bacteria induce neutrophil activation and increase lifespan, potentially causing accumulation in the FRT and epithelial barrier damage.